2010
DOI: 10.1094/phyto-100-8-0732
|View full text |Cite
|
Sign up to set email alerts
|

The Promise and Pitfalls of Sequence-Based Identification of Plant-Pathogenic Fungi and Oomycetes

Abstract: Sequences of selected marker loci have been widely used for the identification of specific pathogens and the development of sequence-based diagnostic methods. Although such approaches offer several advantages over traditional culture-based methods for pathogen diagnosis and identification, they have their own pitfalls. These include erroneous and incomplete data in reference databases, poor or oversimplified interpretation of search results, and problems associated with defining species boundaries. In this let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 43 publications
0
49
0
2
Order By: Relevance
“…A few nucleotide differences in the ITS region, thus a variation similar to what was detected in this work in single powdery mildew samples, is often considered as a reliable marker in the identification of certain fungal species (Bridge et al 2003;Nilsson et al 2008) especially if this is supported by sequences retrieved from GenBank. However, GenBank data have frequently been criticized for inaccuracies from several points of view (e.g., Bridge et al 2003;Kang et al 2010) including the means of obtaining the genetic information deposited in this database. This work showed that the ITS sequences determined in powdery mildew samples, and eventually deposited at GenBank, might not describe all the existing variation in this DNA region and the routine direct sequencing of the ITS region might mask diversity of these important pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…A few nucleotide differences in the ITS region, thus a variation similar to what was detected in this work in single powdery mildew samples, is often considered as a reliable marker in the identification of certain fungal species (Bridge et al 2003;Nilsson et al 2008) especially if this is supported by sequences retrieved from GenBank. However, GenBank data have frequently been criticized for inaccuracies from several points of view (e.g., Bridge et al 2003;Kang et al 2010) including the means of obtaining the genetic information deposited in this database. This work showed that the ITS sequences determined in powdery mildew samples, and eventually deposited at GenBank, might not describe all the existing variation in this DNA region and the routine direct sequencing of the ITS region might mask diversity of these important pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively they could be false positives in that they lacked explicit taxonomic annotation but nevertheless were easy to assign to a known taxonomic lineage. To minimize these concerns, we examined the 50 largest lineages at the phylum, class, and order levels (as ordered by the number of constituent studies) through BLAST searches in UNITE and the INSDC following Kang et al (2010) and Nilsson et al (2012). The full length of the sequences as they were deposited in INSDC/UNITE, as well as the ITS2 and 5.8S separately, were used for these searches.…”
Section: Sorting Of the List Of Taxa (Sequence Or Study Count)mentioning
confidence: 99%
“…a) BLAST is sensitive to the length and level of sequence conservation of the query and reference sequences, and the user is advised to prune any large parts of the SSU and LSU from the ITS sequences before doing BLAST searches (cf. Kang et al 2010). It sometimes pays off to use only the ITS1 or ITS2 for the searches.…”
Section: Guideline 4 Sequences Can Be Broken In Other Puzzling Waysmentioning
confidence: 99%